If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sec(2x) + tan(x) = 1 Remove parenthesis around (2x) ces * 2x + tan(x) = 1 Reorder the terms for easier multiplication: 2ces * x + tan(x) = 1 Multiply ces * x 2cesx + tan(x) = 1 Multiply ant * x 2cesx + antx = 1 Reorder the terms: antx + 2cesx = 1 Solving antx + 2cesx = 1 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2cesx' to each side of the equation. antx + 2cesx + -2cesx = 1 + -2cesx Combine like terms: 2cesx + -2cesx = 0 antx + 0 = 1 + -2cesx antx = 1 + -2cesx Divide each side by 'ntx'. a = n-1t-1x-1 + -2cen-1st-1 Simplifying a = n-1t-1x-1 + -2cen-1st-1 Reorder the terms: a = -2cen-1st-1 + n-1t-1x-1
| a-(-16)=11 | | 5c^3-15c^2+10c=0 | | 3r+9=-3(8r-3) | | 3r+9=24+9 | | 7+15x+2x^2= | | log(5)(5x+6)=2 | | tanx=cotx | | 0.5r+7=9 | | -4c+4c-2= | | -5(7r+5)=31-7r | | 5x^2-2x-16=2x^2+6x | | 2cos(2x)-cos(x)=0 | | logx+2(0)16=4 | | 7r^2-19r-14=-3r+1 | | 30x^2-20x-28=5x^2+4 | | X/2=62 | | V/2=62 | | 3x(-7x^4y)= | | 25n^2+4n-1=1-5n^2 | | 1.13=ln(x/1) | | -6(8-8p)-7=-15+8p | | 25n^2+4n-1=1-5n | | 1-6(-8k-2)=109 | | 8y+96=3y-9 | | x=23000-(x(.12))+(x(.05)) | | 2m+5=8 | | a+14=17 | | x=23-(x(.12))+(x(.05)) | | log(x)+log(x^4)=5 | | 92=-(-5x-4)+6x | | 3(3a-4)=-84 | | 7a^2-14a=21 |